2019
DOI: 10.1002/bab.1799
|View full text |Cite
|
Sign up to set email alerts
|

Combinational effect of angiotensin receptor blocker and folic acid therapy on uric acid and creatinine level in hyperhomocysteinemia‐associated hypertension

Abstract: Homocysteine [HSCH2CH2CH(NH2)COOH] (Hcy) is a sulfur‐containing amino acid of 135.18 Da of molecular weight, generated during conversion of methionine to cysteine. If there is a higher accumulation of Hcy in the blood, that is usually above 15 µmol/L, it leads to a condition referred to as hyperhomocysteinemia. A meta‐analysis of observational study suggested an elevated concentration of Hcy in blood, which is termed as the risk factors leading to ischemic heart disease and stroke. Further experimental studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 97 publications
0
11
0
1
Order By: Relevance
“…Interestingly, among patients with PCOS, homocysteine levels may predict pregnancy outcome, being higher in PCOS patients with recurrent pregnancy loss compared with fertile PCOS controls ( 173 ). Hyperhomocysteinemia predicts the risk of developing atherosclerosis in patients with MetS ( 174 ) and it is a risk factor for ischemic heart disease and stroke ( 175 ). A meta-analysis has shown that folic acid lowers the risk of stroke by 10% and of overall CVD by 4% in patients with hyperomocysteinemia ( 176 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, among patients with PCOS, homocysteine levels may predict pregnancy outcome, being higher in PCOS patients with recurrent pregnancy loss compared with fertile PCOS controls ( 173 ). Hyperhomocysteinemia predicts the risk of developing atherosclerosis in patients with MetS ( 174 ) and it is a risk factor for ischemic heart disease and stroke ( 175 ). A meta-analysis has shown that folic acid lowers the risk of stroke by 10% and of overall CVD by 4% in patients with hyperomocysteinemia ( 176 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study (Figure 1), a total of 170 (85%) patients presented with the etiology of a road traffic accident which is higher than 64% (highest in sample size) as found by Septa et.al, 7 54% as found by Cheema et al, 8 and 29.6% (highest in sample size) as found by Kunz et al 9 Since most of the patients with orbital involvement were associated with road traffic accidents, statistical analysis was done to compare the frequencies which came out to be nonsignificant. Diagnosis of these trauma patients was confirmed for orbital involvement on the basis of clinical features and diagnostic aids as was similarly performed by Jin et al 10 CT is a gold standard to assess the bony orbit status 11,12 . The Water's view is most helpful in evaluating patients with fractures of the inferior orbit and orbital rims 13,14 …”
Section: Discussionmentioning
confidence: 93%
“…Throughout the result, organic solvent modifications are mostly avoided when glycocalyx is detected throughout fast frozen tissues. [ 26–28 ]…”
Section: Main Methods For Studying/visualizing Glycocalyxmentioning
confidence: 99%